Kajian Kasus: Periodontitis Kronis pada Pasien dengan Riwayat Diabetes Melitus - Aris Aji Kurniawan; Anis Sevia Pramaeswari; Anindita Laksitasari (Fakultas Kedokteran Gigi Universitas Jember, 2018)
Chronic periodontitis is an inflammatory disease that occurs in periodontal tissue. The causes of chronic periodontitis can be local and systemic factors. Local factors that can cause chronic periodontitis are plaque accumulation, while systemic factors can be in the form of systemic diseases such as diabetes mellitus. The purpose was to explain the condition of chronic periodontitis that occurs in patients with diabetes mellitus. A 52-year-old woman complained that her teeth have been rocking for about a year. The patient is known to have a history of diabetes mellitus and is undergoing routine treatment. Clinical examination of the oral cavity shows gingival recession in the anterior and posterior teeth area of both the maxilla and mandible, accompanied by the shakiness of the teeth. Patients with diabetes mellitus have decreased immune response and cell function. This condition can inhibit the process of tissue repair and bacterial destruction, to increase the severity of periodontal conditions. the condition of periodontitis can also affect the severity of diabetes mellitus. Conclusion: Periodontitis and diabetes mellitus have a mutually influential relationship.